Project-based learning and assessment of an IT module in an ODL context - Goosen, Leila; van Heerden, Dalize (South African Journal of Higher Education, 2016)
This article introduces project-based learning and assessment in an Information Technology (IT) module offered in an Open Distance Learning (ODL) context. The literature review explains the main arguments relating to project-based learning and assessment in terms of the module researched. The methodology used (an e-mail survey) to investigate the influence of an intervention to enhance student success is described. The findings presented show that the majority of respondents experienced an increase in the effectiveness of teaching for successful learning in an ODL context. Most students believe that sufficient information had been provided to complete their projects successfully, which also helped improve their self-confidence. This article also includes recommendations and implications for the possible future use of project-based learning and assessment in similar modules. In conclusion, the way in which project-based learning and assessment assists in solving problems experienced in a vocational IT module offered in an ODL context is summarised.